Superfícies eletromagnéticas de microondas com controle do regime de trapped-mode - KAWAKATSU, Marcelo Nobuyuki (Universidade Federal do Pará, 2012)
In this work frequency selective surfaces (FSSs) with high quality factor (Q-factor) resonance and polarization independence for a normally incident plane wave were investigated. These FSSs are based on a planar array of metallization on a substrate. A high Q-factor is obtained by excitation of trapped-mode and polarization independence by means of high rotational symmetry of the elements that compose the array. For the design of FSSs with trapped-mode regime control, substrates made of materials with the possibility of controlling their electric or magnetic properties (magnetized ferrite or optically activated silicon) were used. The two concentric rings array on a dielectric substrate analyzed in this work presents a trapped-mode resonance with a Q-factor around 12 and maximum transmittance of 70 %. With the utilization of a magnetized ferrite substrate in this array, it is shown that we can shift the resonance frequency of the trappedmode around 20 % without significant degradation of the transmission resonance. With the use of an optically activated silicon substrate, it is demonstrated the possibility of an almost complete switching of the transmission band in that array. To perform the computer simulations the spectral domain moment method (SDMM) and the commercial programs Ansoft Designer 5 PlanarEM and CST 2009 were used.